Kadar Gula Reduksi, Sukrosa, Serta Uji Hedonic pada Hard Candy dari Penambahan Ekstrak Jagung Manis (Zea mays saccharata), Sukrosa, dan Madu - Rifqi, Muhammad; Sumantri, Nabila Oktri; Amalia, Lia (JURNAL AGROINDUSTRI HALAL, 2022)
Hard candy is a product made from sucrose, glucose, water, and has a hard, transparent, and glossy texture. This study aims to determine the levels of reducing sugar, sucrose, and hedonic in hard candy from the addition of sweet corn extract, sucrose, and honey. 100 g, 95 g, 90 g) and factor B is the concentration of sucrose and honey (60 g:10 g, 55 g: 15 g, 50 g: 20 g). Data analysis used was ANOVA with Duncan’s Advanced Test with a 95% confidence interval. The results showed that the addition of various concentrations of sweet corn extract, sucrose, and honey had a significant effect on the hard candy produced based on the levels of reducing sugar and saccharose, as well as hedonic color, texture, and overall, while the hedonic aroma and taste did not significantly affect the hard candy produced. The reducing sugar content of hard candy ranged from 11.86%-12.59%, the saccharose content of hard candy ranged from 57.13%-76.78, the hedonic results from hard candy showed that the panelists liked the color, aroma, taste, textures, and overalls.